A RESPONSE TO DAVID HOLLENBACH AND SOHAIL H. HASHMI - Oh, Irene (Journal of religious ethics, 2010)
Irene Oh affirms that religious freedom, faith, and reason, as David Hollenbach suggests, are subject matters that offer promising platforms for interreligious dialogue between Christians and Muslims. The need for cross-cultural understanding is imperative especially given the current political climate, in which world leaders can easily exacerbate existing tensions through the misapplication of such terms. Sohail H. Hashmi addresses the need to discuss women's rights as part of a larger discussion on human rights in Islam. Oh concurs and notes that Sayyid Qutb's remarks on women in the United States serve as a starting point for clarifying women's agency in Islam.